Pembuatan Peniti Kain, Panjang 50 mm, Diameter Kawat 0,5 mm, Kapasitas 30 Unit/Jam - Kurnia Idris Maulana; Syamsul Hadi; Achmad Rio Ananta Pratama; Risky Nur Iswanto; Ahmad Firman Dani (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Import of fabric safety pin products is still a problem faced in the market. The purpose of manufacturing is to obtain safety pins from low carbon steel wire measuring 50 mm in length and 0.5 mm in diameter and a circular curve with a diameter of 6 mm. The manufacturing method includes: design of wire bending equipment and equipment for forming the pinhead plate and the base of the pinhead, selection of raw materials of AISI1045 steel wire and pinhead steel plate, making the pointed tip with automatic sanding, bending the pinhead and forming the pinhead plate with a thickness of 0.5 mm, cutting the base of the wire, clamping between the base of the pinhead and the clamping head plate where the part that holds the end of the wire must be positioned correctly, electroplating black chromium on the assembled pinhead, checking the quality of dimensions, symmetry, and evenness of the nickel layer, packaging and labeling. The manufacturing results are medium carbon steel wire pins measuring 50 mm in length and 0.5 mm in diameter coated with black chromium, production costs of IDR 250,-/unit, and a process duration of 2 minutes/unit which implies that the binding between 2 pieces of cloth with the pin can be tied quite strongly.